The Israel economy : the first decade - Patinkin, Don.; The Falk Project for Economic Research in Israel (Jerusalem: Falk Project for Economic Research in Israel, 1959)
This volume examines the Israeli economy with particular reference to: immigration, population, labour force and unemployment; the growth of national income; investment, saving and the import surplus; the inflationary process; and progress toward economic independence.
Includes bibliographical references and index.
lje 2/10/18
Loans
Keywords: Economic development; Economic conditions; Economic history; Israel